BAMBOO SPECIES (POACEAE: BAMBUSOIDEAE) FROM SELAYAR ISLAND - Alin Liana; Purnomo Purnomo; Issirep Sumardi; Budi Setiadi Daryono (PTTI, 2017)
Alin Liana, Purnomo, Issirep Sumardi & Budi Setiadi Daryono. 2017. Jenis-jenis Bambu (Poaceae: Bambusoideae) dari Pulau Selayar. Floribunda 5(6): 185–191. — Delapan spesies dan satu varietas Bambusoideae dilaporkan pertama kali dari Pulau Selayar di Sulawesi Selatan. Berdasarkan hasil survei yang dilakukan, jenis-jenis tersebut yaitu Bambusa blumeana Schult.f., Bambusa maculata Widjaja, Bambusa vulgaris Schard., Bambusa vulgaris Schard. var. vittata, Bambusa sp., Dendrocalamus asper (Schult.) Backer, Gigantochloa atter (Hassk.) Kurz, Schizostachyum blumei Ness, dan Schizostachyum brachycladum (Kurz) Kurz. Deskripsi taksonomis dan gambar disajikan.Kata Kunci: Bambu, Pulau Selayar, Sulawesi.Alin Liana, Purnomo, Issirep Sumardi & Budi Setiadi Daryono. 2017. Bamboo Species (Poaceae: Bambusoideae) from Selayar Island. Floribunda 5(6): 185–191. — Eight species and one variety of Bambusoideae are reported for the first time from Selayar Island in South Sulawesi. Based on the results of field survey, those species are namely Bambusa blumeana Schult.f., Bambusa maculata Widjaja, Bambusa vulgaris Schard., Bambusa vulgaris Schard. var. vittata, Bambusa sp., Dendrocalamus asper (Schult.) Backer, Gigantochloa atter (Hassk.) Kurz, Schizostachyum blumei Ness, and Schizostachyum brachycladum (Kurz) Kurz. Taxonomic descriptions and figures are provided.Keywords: Bamboo, Selayar Island, Sulawesi.